2017
DOI: 10.1007/s12098-017-2372-7
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Bronchoscopy in Non-resolving Pneumonia

Abstract: Non-resolving pneumonia is often an area of clinical dilemma. Bacterial infections are the commonest etiology. Non-infectious causes like tracheobronchomalacia and foreign body aspiration are other important etiologies to be looked for. Early bronchoscopy and bronchoalveolar lavage analysis can play a crucial role in the evaluation of these patients and may provide an important clue or strongly support the specific diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…In view of the prediction, the nomogram could serve as a tool to select patients for evaluating the necessity of flexible bronchoscopy. In general, the presence of persistent atelectasis in chest imaging is a strong indicator for flexible bronchoscopy intervention 27,28 . Thus early bronchoscopic examination may be necessary for children with MPP presented with clinical sign of atelectasis, regardless of the presence of BMP.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the prediction, the nomogram could serve as a tool to select patients for evaluating the necessity of flexible bronchoscopy. In general, the presence of persistent atelectasis in chest imaging is a strong indicator for flexible bronchoscopy intervention 27,28 . Thus early bronchoscopic examination may be necessary for children with MPP presented with clinical sign of atelectasis, regardless of the presence of BMP.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, culture of the tracheal aspirate has a high chance of contamination with colonizing microorganisms [12]. BAL microbiology is a very good marker for the diagnosis of lung infection [13]. In a study by Wang, et al [14] on risk factors of extubation failure in ELBW infants, atelectasis was also found as one of the causes of extubation failure.…”
Section: Discussionmentioning
confidence: 99%
“…Most common infectious etiology identified from BAL was bacterial as in most other studies. 7 Effriti et al in their study had reported microbial isolation rates close to 20%. 8 The bacterial isolation rates from BAL in our study was significantly higher at 25% and in 3 of those cases a change in antibiotics led to improvement of patient condition.…”
Section: Discussionmentioning
confidence: 85%